2022
DOI: 10.3390/nu14163276
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy and Fetal Growth Restriction: Clinical Characteristics and Placental Lesions and Possible Preventive Nutritional Targets

Abstract: Background: The purpose of this study was to describe the placental lesions in pregnancies complicated by hypertensive disorders (HDP) and/or fetal growth restriction (FGR) and in uneventful control pregnancies. Methods: This is a case control study that included singleton pregnancies with HDP and normally grown fetus (HDP-AGA fetus), with HDP and FGR, early FGR, late FGR, and uneventful pregnancies. Feto-placental Doppler velocimetry and sFlt-1/PlGF ratio were performed. Placental histology was evaluated blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…101,102 Mediterranean diet, intake of micronutrients (folic acid) and other factors (gut microbiome) 15,16,17 could prevent HPD related to metabolic syndrome. [103][104][105] As for pre-pregnancy therapy in chronic hypertensive patients, preliminary data suggest a role of Calcium Channel Blockers, ACE inhibitors, and Angiotensin Receptor Blockers as protective factors for complications in pregnancy. 4 This protective influence might be due to their action on the cardiovascular profile and cardiac structure in those patients taking these medications at least 1 year prior to pregnancy, which probably leads a more favorable cardiac geometry and cardiovascular hemodynamics right before pregnancy.…”
Section: B Possible Interventions Before Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…101,102 Mediterranean diet, intake of micronutrients (folic acid) and other factors (gut microbiome) 15,16,17 could prevent HPD related to metabolic syndrome. [103][104][105] As for pre-pregnancy therapy in chronic hypertensive patients, preliminary data suggest a role of Calcium Channel Blockers, ACE inhibitors, and Angiotensin Receptor Blockers as protective factors for complications in pregnancy. 4 This protective influence might be due to their action on the cardiovascular profile and cardiac structure in those patients taking these medications at least 1 year prior to pregnancy, which probably leads a more favorable cardiac geometry and cardiovascular hemodynamics right before pregnancy.…”
Section: B Possible Interventions Before Pregnancymentioning
confidence: 99%
“…101,102 Mediterranean diet, intake of micronutrients (folic acid), and other factors (gut microbiome) [15][16][17] could prevent HDP related to metabolic syndrome. [103][104][105] As for prepregnancy therapy in chronic hypertensive patients, preliminary data suggest a role of calcium channel blockers, ACE inhibitors, and angiotensin receptor blockers as protective factors for complications in pregnancy. 4 This protective influence might be due to their action on the…”
Section: Possible Interventions Before Pregnancymentioning
confidence: 99%
“…The basic clinical characteristics of pregnant women included in our model were smoking or passive smoking, gravidity and history of hypertension. These factors may impair the function of trophoblast cells to varying degrees, and affect blood vessel generation and remodeling, thereby influencing the establishment and maintenance of a stable fetal supply of nutrition and oxygen through the placenta [25][26][27] . However, clinical characteristics alone exhibited a relatively poor predictive performance for FGR.…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most common contributing factors is placental insufficiency ( 4 ), a condition that also serves a role in the pathogenesis of hypertensive disorders of pregnancy (HDP), including preeclampsia ( 5 ). In a recent study, it was demonstrated that FGR-HDP, a condition with significant obstetric morbidity and mortality, exhibits maternal vascular malperfusion of the placental bed, abnormal feto-placental Doppler parameters and signs of oxidative stress of the syncytiotrophoblast ( 6 ). Other recent studies show that extracellular vesicles derived from placental tissue influence endothelial cell function, explaining the relationship between placental insufficiency and hypertensive disorder ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%